Analysis Of Factors Associated With Low Back Pain In Dentists In Jambi City - Rini, Willia Novita Eka; Aswin, Budi; Nuzulul, Ashar (International Journal of Health Sciences, 2025)
Low back pain (LBP) is a common complaint experienced by workers in various sectors including dentists. LBP can cause limited physical activity and decreased productivity and quality of work. The purpose of this study was to analyse the factors associated with the incidence of low back pain in dentists. This research used a cross-sectional study design with a sample of 134 dentists selected by purposive sampling. Data were collected through a characteristic questionnaire, Low Back Pain Disability (ODI) Questionnaire, Rappid Upper Limb Assessment (RULA) observation sheet, then analysed using the chi- square test in SPSS version 26.0.The results showed that the variables of work posture, BMI and length of work were the most influential variables on the incidence of LBP. Respondents who have abnormal BMI have a risk of 10.65 times the incidence of NCD. Based on the results of the study it can be concluded that low back pain in dentists is related to work posture, BMI, and length of work.